Penerapan Pencarian Metode Sequential Dalam Sistem Informasi Persediaan Pada PO Irama Vision Pontianak - Thommy Willay (Universitas Katolik Musi Charitas, 2019)
At present, the development of information technology in the world is very rapid. The use of information technology is very helpful in completing human tasks. With the existence of information technology, can improve work efficiency and effectiveness to support success in achieving company goals. In its development, almost all companies are trying to make changes to the existing work systems. The system of PO Irama Vision is still conventional as data must be recorded or manual data search so it is can cause errors that result in inaccurate reports received. An inventory information system is designed and is expected to be able to process inventory data and sales of goods better and can improve work efficiency and business processes can run more efficiently. Data search using the sequential method means that search data is searched according to the initial order to the end based on the search key entered by the user. Searching is faster and more accurate when compared to old systems. The other goal is, generally expected to be able toimprove company performance and also increase satisfaction for buyers.